Association between polymorphisms in IL27 and risk for CHD in a Chinese population. (9th February 2015) - Zhang, Danyan; Ma, Mingfu; Yang, Yuyou; Wan, Ling; Yang, Zhixi; Lv, Jing; Li, Xinsheng; Yang, Hao; Huang, Pei; Li, Lianbing
Abstract: Background: IL-27, a member of the IL-12 family, has been involved in maternal tolerance to the foetus and successful pregnancy. Growing evidences indicate that IL-27 plays a crucial role in pregnancy. Aim: We carried out the present study in order to investigate whether polymorphisms in the IL27 are associated with the risk for CHDs, including atrial septal defect and ventricular septal defect. Patients and methods: We conducted this case–control study among 247 atrial septal defect patients, 150 ventricular septal defect patients, and 368 healthy controls in a Chinese population using polymerase chain reaction-restriction fragment length polymorphism assay. Results: Significantly increased risk for atrial septal defect (p=0.001, OR=1.490, 95% CI=1.178–1.887) and ventricular septal defect (p=0.004, OR=1.502, 95% CI=1.139–1.976) was observed to be associated with the allele G of rs153109. In a dominant model, we have also observed that increased susceptibilities for atrial septal defect (p<0.01, OR=1.89, 95% CI=1.35–2.63) and ventricular septal defect (p<0.01, OR=2.50, 95% CI=1.67–3.85) were statistically associated with rs153109; however, no association was found between CHD risk and rs17855750 in the IL27 gene. Conclusion: The 153109 of the IL27 gene may be associated with the susceptibility to CHD, including atrial septal defect and ventricular septal defect.